2019
DOI: 10.3390/nu11081825
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Anabolic Properties of Plant- versus Animal-Based Protein Sources in Supporting Muscle Mass Maintenance: A Critical Review

Abstract: Plant-sourced proteins offer environmental and health benefits, and research increasingly includes them in study formulas. However, plant-based proteins have less of an anabolic effect than animal proteins due to their lower digestibility, lower essential amino acid content (especially leucine), and deficiency in other essential amino acids, such as sulfur amino acids or lysine. Thus, plant amino acids are directed toward oxidation rather than used for muscle protein synthesis. In this review, we evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
212
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(267 citation statements)
references
References 115 publications
3
212
0
13
Order By: Relevance
“…A second point, which concerns protein quality: plant-based proteins have a lower anabolic potential than those animal-based [57]. Two strategies can be useful to ensure the intake of essential amino acids in plant-based diets: increase the intake of proteins and improve the quality of those present in the diet [58].…”
Section: Discussionmentioning
confidence: 99%
“…A second point, which concerns protein quality: plant-based proteins have a lower anabolic potential than those animal-based [57]. Two strategies can be useful to ensure the intake of essential amino acids in plant-based diets: increase the intake of proteins and improve the quality of those present in the diet [58].…”
Section: Discussionmentioning
confidence: 99%
“…Third, we had no data about the foods consumed (e.g., meat, dairy, and grains). Protein sources are important because animal protein has a higher anabolic effect than vegetable proteins; this effect is mainly attributable to higher amino acid availability in animal-based foods than those coming from plant-based foods [ 52 ]. Therefore, the inclusion of data of ingested foods and food intake patterns along the determination of IPI per day and per meal might help to understand their combined role on health-related variables and which foods are associated with a lower probability of inadequacy [ 19 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these people with functional limitations may receive support in the provision of food, for example, from relatives or friends, which is why their own eating motivation is less reflected in their eating behavior. Animal-based protein sources are regarded as highly relevant for muscle functioning [7,17,58,59]; nevertheless, it is to date still discussed to what extent distinct protein sources affect different domains of physical function. For example, Coelho et al [60] and Gazzani et al [61] both identified a positive association of walking speed and plant-based protein ingestion.…”
Section: Role Of Functional Statusmentioning
confidence: 99%